The Influence of Product Quality on Customer Satisfaction at KFC Pettarani Branch, Makassar City - Virah Aulia (Economics and Business Journal (ECBIS), 2023)
This study aims to determine the effect of product quality on customer satisfaction at the KFC pettarani branch in Makassar. The independent variable in this study is product quality, while the dependent variable is customer satisfaction. The population in this study is the customer of KFC Pettarani Makassar City, amounting to 43,000 customers per month, while the sample used is based on the Slovin formula with an error rate of 10%, namely 100 respondents. Withdrawal sampling technique is non-probability sampling with the technique taken is accidental sampling technique. Data was collected using a questionnaire. The data analysis technique used is simple linear regression analysis using SPSS 25.00 for windows. Based on simple linear regression analysis, the results obtained are product quality which affects customer satisfaction. The influence given is positive and significant. The positive direction given by the product quality variable (independent) can be seen from the regression equation as follows: Y = 1.663 + 0.310X. This shows that product quality has a positive and significant effect on customer satisfaction.